Atomically dispersed palladium supported on nitrogen-doped mesoporous carbon for drastic electrocatalytic hydrogen evolution. (1st December 2022) - Wei, Hehe; Su, Zixiang; Deng, Bohan; Wu, Hui; Li, Hui; Zhang, Longtao; Ge, Binghui; Li, Jing; Gong, Xueqing
Abstract: The electrocatalysis of water to hydrogen is expected to play an essential and significant role in the development of future electrochemical energy conversion and storage technologies, together with the exploration of green energy. However, the high cost of noble metal catalysts remains a key challenge and it still requires further investigations to fabricate high mass activity and stable electrocatalysts. Herein, we report a facile and economical approach to achieve atomically dispersed palladium on the nitrogen-doped mesoporous carbon matrix (Pd1 /NMC) as the electrocatalyst for hydrogen evolution, which exhibits an overpotential of 37 and 118 mV at the current density of 10 and 100 mA cm −2, respectively, superior to the commercial platinum/carbon (Pt/C) and palladium/carbon (Pd/C) catalysts. Moreover, the mass activity of the Pd1 /NMC catalyst surpasses that of Pt/C and Pd/C at 100 mV versus RHE in HER. Systematic characterizations demonstrate that the Pd atoms are atomically dispersed on the surface of NMC and stabilized by active nitrogen sites, inducing the isolated Pd atoms to form a favorable bivalent oxidation state. This method provides an atomic-level insights into preparing superior single-atom catalysts for energy-related applications and devices. Graphical abstract: Atomically dispersed palladium supported on nitrogen-doped mesoporous carbon catalyst is synthesized via imbalanced annealing process of ink that exhibits such remarkably high activity for electrochemical hydrogen evolution with ultralow overpotentials of 37 and 118 mV at the current density of 10 and 100 mA cm −2, together with superior mass activity and excellent selectivity, superior to state-of-the-art commercial Pt/C and Pd/C catalysts. Image 1 Highlights: Develop an imbalanced annealing process of ink to prepare single-atom materials. Synthesize nitrogen-doped mesoporous carbon supported Pd single-atom catalyst. Exhibit high activity and stability for HER, together with overpotentials of 37 and 118 mV at 10 and 100 mA cm −2 . Achieve high atom utilization efficiency of noble metal, superior to the state-of-the-art commercial Pt/C and Pd/C.